Perancangan Furnitur dengan Material Kayu Balsa - Wijoyo, Sherry Suryani; Santosa, Adi; Pradjonggo, Celine Junica (Intra, 2018)
Balsa wood (Ochroma pytamidale) is one of the lightest plants that grow fast (called Fast Growing Species or FGS). This advantage can fulfill the public needs of wood as the material of interior product. In addition, people currently need a flexible, movable and lightweight interior product for narrow spaces. As one of the lightest wood, Balsa wood can overcome this public need. However, Balsa wood is not commonly used in Indonesia as the interior product material. It is undeniable that this type of wood need a special treatment because Balsa wood has a lower level of density than other wood types. That fact makes Balsa wood is quite doubtful from the construction aspect. The authors conducted several experiments related to joining, finishing, and form of balsa wood. As the result, type of joints that suitable for this wood type are Half-lap and also Mortise-tenon. Based on Scandinavian style, the design concept is universal and simple. Furthermore, the author has not found an effective and efficient wood finishing which can cover wood’s deficiency, thus it needs further research